Feature detection of mitral valve based on image processing technique: A review - Mahadi, Lina Farhana; Ibrahim, Nabilah; Zaluwi, Mohd Thariq; Johan, Muhammad Haniff S.M. (Journal of physics. Conference series, 2019)
Mitral valve prolapse is a standout amongst the most common heart conditions, which may influence up to five to 10% of typical populace and a standout amongst the most questionable ones. The advent of computer aided technologies has contributed widely in medical application. This paper discussed on a methodological study on medical image processing to evaluate accurate diagnosis in the field of computer vision. The fundamental of image processing is to enhance the raw images obtain from machine so the useful information can be extracted from it. This paper deals with the application of the image processing on mitral valve images for further research purpose. Ultrasound data taken with subject diagnosed by mitral valve disease is analyse to determine the diameter of the valve. Based on the experiment, the average of mitral valve diameter is 21.82 mm which represent the abnormal length of mitral valve for adult.